SARS-CoV2, the COVID-19 Pandemic and Community Perceptions. (February 2021) - Keene Woods, Nikki; Vargas, Inneké; McCray-Miller, Melody; Drassen Ham, Amy; Chesser, Amy K.
The purpose of this study was to describe knowledge and beliefs about SARS-CoV2 and COVID-19 and explore the gaps between current media coverage of health risks and what the general public knows about the virus and its outcome. A 37-question survey was developed and administered to a community collaborative group in a Midwestern state in the United States. Fifty-three participants completed the survey. When asked where participants found their information, a majority reported the internet (33.9%, n = 18/53) and radio and/or tv (28.3%, n = 15/53). Most participants showed a basic level of COVID-19 knowledge, but few could identify the 3 most frequent symptoms of COVID-19 (7.5%, n = 4/53). The results from this study highlight the continued need for increased public health communication. Educational efforts should focus on social media and internet outlets to address COVID-19 misinformation, strategies to address vaccine hesitancy, and the associated communication gap to help address related health disparities.